Collaborative feasibility study of a biphasic system (Roche Septi-Chek AFB) for rapid detection and isolation of mycobacteria. - Isenberg, H D (1991)
A study to delineate the feasibility of a biphasic-culture approach for detection and isolation of mycobacteria from clinical specimens except blood was conducted in four medical centers. The biphasic system (Septi-Chek AFB, Roche Diagnostic Systems, Nutley, N.J.) was compared with conventional mycobacterial isolation media and the BACTEC system. Septi-Chek AFB showed the highest degree of mycobacterial recovery. In addition, Septi-Chek AFB consistently shortened the time required for recovery of mycobacteria from clinical specimens and supported the growth of small inoculum numbers of stock cultures of 14 mycobacterial species. The study indicates the feasibility and potential advantages of the biphasic approach for detection and isolation of mycobacteria.